The lipid peroxidation products as possible markers of Alzheimer's disease in blood - Skoumalová, A; Ivica, J; Santorová, P; Topinková, E; Wilhelm, J (Experimental gerontology, 2011)
Oxidative stress, which is present in Alzheimer's disease (AD), results in the formation of various end-products of free radical reactions with proteins and lipids. At present there are no reliable diagnostic biomarkers of AD in the blood. Therefore, specific products of lipid peroxidation in the blood of AD patients were investigated. Lipophilic extracts of erythrocytes in the group of patients with AD (n = 44) and age-matched controls (n = 16) were studied. The end-products of lipid peroxidation, so called lipofuscin-like pigments (LFP), were analysed by fluorescence spectroscopy. It was found that the level of these products is significantly increased in erythrocytes of AD patients compared to controls. LFP were further separated by means of HPLC into individual fractions to study their composition in AD and controls. The specific fraction of LFP in AD patients, which was isolated, might represent a disease-specific product in the blood.
Keywords: oxidační stres; Male; biologické markery; fluorescenční spektrometrie; Biomarkers; vysokoúčinná kapalinová chromatografie; Lipofuscin; Alzheimerova nemoc; Alzheimer Disease; Aged; mužské pohlaví; senioři; lipofuscin; Chromatography, High Pressure Liquid; senioři nad 80 let; lidé; ženské pohlaví; Humans; Aged, 80 and over; erytrocyty; peroxidace lipidů; Erythrocytes; Lipid Peroxidation; Spectrometry, Fluorescence; Female; Oxidative Stress